PENGARUH TRANSFORMASI DIGITAL, PELATIHAN BERBASIS TEKNOLOGI, DAN BUDAYA ORGANISASI TERHADAP PRODUKTIVITAS KARYAWAN (STUDI PADA UKM MAKANAN DAN MINUMAN DI KECAMATAN BARUGA KOTA KENDARI, INDONESIA) - Suprianto, Ghalib; Mahrani, Sri Wiyati (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze the effect of digital transformation, technology-based training, and organizational culture on employee productivity in food and beverage Small and Medium Enterprises (SMEs) located in Baruga District, Kendari City. The research uses a quantitative approach with a survey method. Data were collected through structured questionnaires distributed to employees. The population consists of employees working in food and beverage SMEs in Baruga District. A total of 116 respondents were selected using purposive sampling, with criteria including employees who have worked for at least two years and are involved in operational activities. Data were analyzed using multiple linear regression. The results indicate that digital transformation, technology-based training, and organizational culture have a positive and significant effect on employee productivity, both partially and simultaneously. Among these variables, digital transformation has the most dominant influence.